General characteristics of normal and stress-enhanced protein degradation in Lemna minor (duckweed). - Cooke, R J (1980)
The general features of protein degradation in Lemna minor were studied by using a double-isotope technique. In common with several animal systems, there are correlations between the relative rate of protein degradation on the one hand and molecular weight, charge and carbohydrate content on the other. Large proteins, acidic proteins and non-glycosylated proteins are degraded relatively more rapidly than small or basic proteins, or glycoproteins. The correlations with size and carbohydrate content are explicable on the basis of differential susceptibility to Pronase, whereas the charge correlation cannot be explained on the basis. In addition, acidic proteins are not generally of higher molecular weight than neutral or basic proteins. The correlations are found in fronds growing in normal complete medium and in fronds transferred to medium lacking nitrate of made 50% (v/v) with respect to deuterium oxide, both of which are conditions that induce a large increase in protein breakdown in Lemna. Thus basal protein degradation and enhanced degradation do not appear to differ fundamentally in their general characteristics. The results are discussed in relation to the reported features of normal and enhanced proteolysis in animal tissues and to the possible mechanism of protein degradation in Lemna.